Kajian Teori Pengendalian Manajemen dan Pengukuran Kinerja Strategis - Mohamad Ajib Markaban Mahiri; Hidayatul Lutfiah; Nur Afifah; Ahmad Sodiq (JMB : Jurnal Manajemen dan Bisnis, 2023)
In this study, we will try to discuss management control, where management control is an important thing for companies to do to help achieve their goals. This study uses a qualitative descriptive research method by conducting an exploratory study of the literature. The data collection technique uses library study techniques. Literature study is an activity of collecting data from various sources or literature needed in research such as documents, books, magazines, historical stories, and so on. Management control is a system in determining the strategy implemented and efforts to achieve organizational goals through the control function of every activity that occurs. Another element that can be expected to support the achievement of a company's goals is the measurement of employee performance. Good management control will improve the performance of employees in the organization and increase investment opportunities.